An Analysis on Code Switching in "Dealova" Novel - JMMatai PSDKU; Luisi Amilia Metriani (MATAI: International Journal of Language Education, 2021)
Language means communication with other, where we need to build the relation to get the better understanding. It is used by people to give a message and information where everyone speaks, or identifies with one language. Beside that it is always develops every era according to the communication model used in writing or speaking. This research is aimed to give some contribution to the readers and to enrich the reader’s knowledge about code switching. Therefore, the writer hopes that it will be useful for English students especially those who are studying sociolinguistics. Moreover, code switching have some types to applying in every situational based on the type of the type of codeswitching.to give different sense especially for teenager. The code switching can stimulate the reader to interest read a book, a novel, a newspaper and gives a good influence in order to improve the vocabulary in English.